2021
DOI: 10.2147/ijgm.s287506
|View full text |Cite
|
Sign up to set email alerts
|

Biological Significance of 18F-FDG PET/CT Maximum Standard Uptake Value for Predicting EGFR Mutation Status in Non-Small Cell Lung Cancer Patients

Abstract: Purpose To investigate the potential of maximum standardized uptake value (SUVmax) in predicting epidermal growth factor receptor ( EGFR ) mutation status in non-small cell lung cancer (NSCLC) patients. Methods Clinical data of 311 NSCLC patients who had undergone both EGFR mutation test and 18 F-FDG PET/CT scans between January 2013 and December 2017 at our hospital were retrospectively an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…However, opposite results could be observed that the metabolic activity of 18 F-FDG (e.g., SUV max ) in NSCLC EGFR-mutant patients was significantly higher than that of wild-type patients ( 25 , 52 54 ). The expression status of EGFR protein was also evaluated, and higher SUV max was positively correlated with EGFR overexpression ( 59 , 60 ).…”
Section: Clinical Correlation Between Epidermal Growth Factor Recepto...mentioning
confidence: 80%
“…However, opposite results could be observed that the metabolic activity of 18 F-FDG (e.g., SUV max ) in NSCLC EGFR-mutant patients was significantly higher than that of wild-type patients ( 25 , 52 54 ). The expression status of EGFR protein was also evaluated, and higher SUV max was positively correlated with EGFR overexpression ( 59 , 60 ).…”
Section: Clinical Correlation Between Epidermal Growth Factor Recepto...mentioning
confidence: 80%
“…Liu et al showed that MTV were lower in NSCLC patients harboring EGFR mutations than in patients bearing wild-type EGFR [ 39 ]. It was found, however, conversely, that patients with NSCLC harboring EGFR mutations had significantly higher metabolic activity of 18 F-FDG (e.g., SUV max ) as compared to patients with wild-type EGFR [ 40 , 41 ]. Even no significant difference in 18 F-FDG uptake between EGFR mutant and wild-type NSCLC patients has also been reported [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the radiotranscriptomics of EGFR did not improve on the current state-of-the-art study of Rizzo et al [ 23 ], which was based solely on semantic CT features. This can also be attributed to the imaging modality, since better and more discriminative features or biomarkers [ 66 ] have been reported in several studies [ 25 , 67 , 68 , 69 ] where the PET/CT radiomic signature with an AUC of 0.805 significantly outperformed the CT only features (AUC 0.667) in EGFR mutation status differentiation. Despite the limited number of patients for machine learning analysis, especially regarding the molecular subtype patient cohorts, the proposed radiotranscriptomic model for KRAS differentiation outperformed the model of Rizzo et al [ 23 ].…”
Section: Discussionmentioning
confidence: 99%